Effects of calf massage on standing discomfort and muscle activity due to prolonged standing in upright position among production line workers - Ramalingam, Kalai Selvan (2019)
Introduction: Many occupations (especially in assembly production lines) require the workers to stand for prolonged periods of time without enough interventions such as breaks or resting periods. Previous studies have shown that prolonged standing is the cause of pain and discomfort in the back and lower limbs. During prolonged standing, the muscles and ligaments undergoes static loading which causes the compression of tissue in the joints and venous pooling in the leg areas which leads to the cause of fatigue. Objective: Therefore, the aims of this study is to determine the effect of intervention (calf massage) on discomfort due to prolonged standing in upright position. Materials and Methods: This study was conducted among male workers at a manufacturing with production line workers. List of all production workers were obtained from HR Department and simple random sampling were done by number categorization. A total of 108 respondents (54 respondents for each control and experimental group) participated in this study. The experiment took place in a room with a similar setup of production line. Each respondent was requested to perform simulated task for 2 hours. For the experimental group, the calf massager was turned on at every 15 minutes. At every 15 minutes interval, respondents from both groups were required to evaluate their discomfort level on Borg’s scale CR-10 questionnaire. Meanwhile, surface electromyography (sEMG) was used to monitor the muscle activity (right and left lower leg around calf area specifically at gastrocnemius and tibialis anterior muscles in both experimental and control groups) throughout the experimental durations. Results and Discussion: The discomfort rating of the experimental group had showed reduction compared to the control group during the testing period. Results revealed that the discomfort rating for lower back, knees, thigh, calf and feet were significantly lower (p<0.05) among experimental group compared to the control group. Muscle activity of respondents showed that there are reductions of electromyography levels for both right and left calf muscles. The results also revealed that there were significant decline (p<0.05) of electromyography levels among experimental group compared to the control group with 2 hour prolonged standing process. Conclusion: This study has provided new insights into the effects of calf massage prototype usage on prolonged standing workers in a controlled laboratory session. The use of calf massage prototype has provided a beneficial ergonomic feature which reduces muscle and body’s discomfort. This also increases the workers comfort with less negative impact on muscle activity. Calf massage prototype could be an intervention that can provide better comfort for prolonged standing and eventually increase worker’s performance.